Lumbar Facet Joint Compressive Injury Induces Lasting Changes in Local Structure, Nociceptive Scores, and Inflammatory Mediators in a Novel Rat Model. (28th June 2012) - Henry, James L.; Yashpal, Kiran; Vernon, Howard; Kim, Jaesung; Im, Hee-Jeong
Abstract : Objective . To develop a novel animal model of persisting lumbar facet joint pain. Methods . Sprague Dawley rats were anaesthetized and the right lumbar (L5/L6) facet joint was exposed and compressed to 1 mm with modified clamps applied for three minutes; sham-operated and naïve animals were used as control groups. After five days, animals were tested for hind-paw sensitivity using von Frey filaments and axial deep tissue sensitivity by algometer on assigned days up to 28 days. Animals were sacrificed at selected times for histological and biochemical analysis. Results . Histological sections revealed site-specific loss of cartilage in model animals only. Tactile hypersensitivity was observed for the ipsi- and contralateral paws lasting 28 days. The threshold at which deep tissue pressure just elicited vocalization was obtained at three lumbar levels; sensitivity atL1 > L 3 / 4 > L6 . Biochemical analyses revealed increases in proinflammatory cytokines, especially TNF- α, IL-1 α, and IL-1 β . Conclusions . These data suggest that compression of a facet joint induces a novel model of local cartilage loss accompanied by increased sensitivity to mechanical stimuli and by increases in inflammatory mediators. This new model may be useful for studies on mechanisms and treatment of lumbar facet joint pain and osteoarthritis.